PENGARUH WORK-FAMILY CONFLICT TERHADAP WITHDRAWAL BEHAVIOR DENGAN STRES KERJA SEBAGAI MEDIASI PADA KARYAWAN PEREMPUAN DI CV. MODENA RATTAN CIREBON - Siti Cholifah; Ali Jufri; Puspa Dewi Yuianty (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the effect of work-family conflict on withdrawal behavior with work stress as a mediating variable among married female employees at CV. Modena Rattan Cirebon. The study reveals that the imbalance between work and family roles increases work stress, which in turn contributes to withdrawal behavior. Regression analysis results show that work-family conflict significantly influences withdrawal behavior, and work stress plays a significant mediating role in this relationship. These findings highlight the importance of stress management and policies that support work-life balance to reduce withdrawal behavior symptoms among female employees. Therefore, companies need to pay attention to work-family balance aspects to improve employee performance and well-being.